National Variability of German Language in Field of Lexical Compatibility (by Material of Austrian and Swiss Collocations) - L. B. Kopchuk (Научный диалог)
The author’s attention is drawn to two problem areas of modern linguistics: the study of lexical compatibility and further development of the concept of national variability of the German language. Collocations are chosen as an object of research. They are considered on the one hand as a basic phenomenon of lexical combinatorics, and on the other hand, as a special type of phraseological units, reflecting the features of all system levels of language or language variant. Based on the comparative analysis of Austrian, Swiss and German collocations extracted from lexicographical sources, the author shows that the norms of lexical compatibility in the German language of Germany, Austria and Switzerland in a number of aspects do not coincide. It is noted that national language standards have a significant number of collocations that are unknown and / or uncommon in other regions of the German-speaking area and in many cases have ethnocultural conditionality. As another kind of nationally specific collocations, the author considers the collocations that have common structural and semantic properties in all three national variants of the German language, but differ in the design of the base or collocator. It is argued that the revealed differences are due to either inventory and semantic differences in the lexical content of the phrases, or the variability of the use of general German components. In addition, the author points out that the national features of collocations are also manifested in the specifics of the syntactic organization, especially in the use of prepositions. Thus, it is shown that the peculiarities of Austrian and Swiss collocations are due to the originality of the national variants of the German language at different levels of the language system.